2006
DOI: 10.1128/aem.72.4.2526-2532.2006
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Bradyrhizobium japonicum Reduces N 2 O Surrounding the Soybean Root System via Nitrous Oxide Reductase

Abstract: Nitrous oxide (N 2 O) is a key atmospheric greenhouse gas that contributes to global climate change through radiative warming and depletion of stratospheric ozone (1, 24). Agricultural land is a major source through denitrification and nitrification (14, 35) and contributes significantly to the net increase in atmospheric N 2 O (1, 34). Several attempts have been made to reduce the emission of N 2 O from agricultural systems (34,35).The complete denitrification of nitrate by bacteria to dinitrogen (N 2 ) is ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 54 publications
(55 reference statements)
3
70
0
Order By: Relevance
“…Mutagenesis targeting the dme gene was performed as reported by Sameshima-Saito et al 20,21) . The dme gene was excised as a 3.3-kb EcoRI fragment, and inserted into the EcoRI site of pK18mob 23) to generate the plasmid pKdme (7.0 kb).…”
Section: Dna Manipulationsmentioning
confidence: 99%
“…Mutagenesis targeting the dme gene was performed as reported by Sameshima-Saito et al 20,21) . The dme gene was excised as a 3.3-kb EcoRI fragment, and inserted into the EcoRI site of pK18mob 23) to generate the plasmid pKdme (7.0 kb).…”
Section: Dna Manipulationsmentioning
confidence: 99%
“…Kim et al (10) found that N 2 O emission from fields with nodulating soybean was several times higher than that from fields with nonnodulating soybean at a flowering stage of soybean growth in the field, suggesting that nodulation enhanced N 2 O emission. On the other hand, Sameshima-Saito et al (17) reported that soybean nodules can take up a low concentration of N 2 O from outside the nodules, equivalent to the natural concentration of N 2 O in the air (approximately 0.31 ppm) and that this uptake depends on the nosZ gene, which encodes N 2 O reductase in Bradyrhizobium japonicum. Therefore, the N 2 O metabolism of nodulated soybean roots is complex, and the mechanism underlying N 2 O emission from soybean fields has not yet been identified.…”
mentioning
confidence: 99%
“…Bradyrhizobium cells were grown at 30°C in HM salt medium supplemented with 0.1% arabinose and 0.025% (wt/ vol) yeast extract (Difco, Detroit, MI) (18). HM medium was further supplemented with trace metals (HMM medium) for the denitrification assay (17). Escherichia coli cells were grown at 37°C in Luria-Bertani medium (16).…”
mentioning
confidence: 99%
“…This strain also has nitrous oxide (N 2 O) reductase activity (25,26,27). The N 2 O that is developed by defective denitrification is a strong greenhouse gas (2,11).…”
Section: Discussionmentioning
confidence: 99%